1992
DOI: 10.1136/adc.67.1_spec_no.36
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of plasma volume in neonates.

Abstract: There is no reliable and safe method for measuring plasma volume in ill newborn infants. We describe an adaptation of the dye dilution technique using indocyanine green as the plasma label, which can be used in the sickest and smallest of infants with the minimum of disturbance. To avoid the need to take large volumes of blood from the infant, samples were diluted 1:1 with distilled water and pooled adult sera was used to construct the dye dilution standard curves. Eighteen preterm and fullterm infants were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
(3 reference statements)
1
18
1
Order By: Relevance
“…It is firmly bound to plasma proteins, excreted in bile in unconjugated form, and rapidly eliminated by the liver within 10 -15 min. ICG has been shown to be safe in adults (27) and when used in newborn and preterm infants (4,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is firmly bound to plasma proteins, excreted in bile in unconjugated form, and rapidly eliminated by the liver within 10 -15 min. ICG has been shown to be safe in adults (27) and when used in newborn and preterm infants (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of a simple cotside method to estimate TCV that could be used shortly after birth would be a useful tool both for the neonatal clinician and the researcher. Methods used previously involving the injection of autologous red cells labeled with biotin (3) or repeated blood sampling following injection of a marker such as indocyanine green (4) are not suitable for routine clinical practice.…”
mentioning
confidence: 99%
“…Furthermore, ICG results in much higher signalto-noise ratio data than does manipulation of SaO 2 . ICG has been used to measure various physiologic parameters such as cerebral blood flow (11), hepatic function (24), plasma volume (25), cardiac output (26), and left-to-right shunts (27) in infants since 1965. One study, involving more than 3000 human subjects, showed that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Volume Determination with ICG PV was assayed and RCV calculated as described by Anthony et al [1], using an ICG solution of 0.25 mg/l. 0.2 mg/kg of ICG was administered as a rapid intravenous injection (over 10 s), and three blood samples (0.5 ml) were obtained at 3, 5 and 7 min after the injection.…”
Section: Patients and Protocolmentioning
confidence: 99%
“…Albumin-binding dyes indocyanine green [1] and Evan's blue [2][3][4] and partial plasma exchange transfusion [5] have previously been applied to assess neonatal PV. These techniques are impractical for most clinical purposes.…”
Section: Introductionmentioning
confidence: 99%